SIGNIFICANTLY STRONG EXPRESSION OF STAT6 AND SSTR2A IN DIFFERENTIATE THE SOLITARY FIBROUS TUMOR / HEMANGIOPERICYTOMA (SFT/HPC) AND MENINGIOMA - bela bagus setiawan (Oceana Biomedicina Journal, 2023)
Background: Solitary fibrous tumor / hemangiopericytoma (SFT / HPC) and fibroblastic types of meningioma have similarities that is difficult to distinguish based on histology. Immunohistochemistry of STAT6 and SSTR2A are definitive biomarkers in both tumors. Inversion-mediated fusions between two genes, NAB2 and STAT6, were detected in SFT / HPC that inducES proliferation in cells. The somatostatin receptor (SSTR) 2 is located on chromosome 17q25.1 which is expressed diffusely in meningiomas. Objective: This study aimed to determine the expression of STAT6 and SSTR2A in SFT/HPC and meningiomas. Methods: An analytical observational study with consecutive sampling on 64 samples diagnosed with SFT/HPC and meningioma. Samples divided into 3 groups, group 1 consisted of grade I meningoma, group 2 consisted of grade II and III meningioma and group 3 consisted of solitary fibrous tumor/Hemangiopericytoma (SFT/HPC). Results: Based on the Mann Withney comparative test, STAT6 expressions showed significant differences in group 1 and 3, as well as group 2 and 3 (P < 0.05). SSTR2A expressions in group 1 and 3, as well as group 2 and 3 also showed significant differences (P < 0.05). Conclusion: Immunohistochemistry of STAT6 and SSTR2A is strongly expressed in SFT/HPC and meningioma. Keywords: Meningeal solitary fibrous tumor (SFT)/hemangiopericytoma (HPC), Meningioma, STAT6, SSTR2A.